Differences in Adipose Tissue and Lean Mass Distribution in Patients with Collagen VI Related Myopathies Are Associated with Disease Severity and Physical Ability - Rodríguez, M. A.; Del Rio Barquero, Luís M.; Ortez, Carlos I.; Jou, Cristina; Vigo, Meritxell; Medina, Julita; Febrer, Anna; Ramon-Krauel, Marta; Diaz-Manera, Jorge; Olive, Montse; González-Mera, Laura; Nascimento, Andres; et al. (Frontiers in Aging Neuroscience, 2017)
Mutations in human collagen VI genes cause a spectrum of musculoskeletal conditions in children and adults collectively termed collagen VI-related myopathies (COL6-RM) characterized by a varying degree of muscle weakness and joint contractures and which include Ullrich Congenital Muscular Dystrophy (UCMD) and Bethlem Myopathy (BM). Given that collagen VI is one of the most abundant extracellular matrix proteins in adipose tissue and its emerging role in energy metabolism we hypothesized that collagen VI deficiency might be associated with alterations in adipose tissue distribution and adipokines serum profile. We analysed body composition by means of dual-energy-X-ray-absorptiometry (DXA) in 30 paediatric and adult COL6-RM myopathy patients representing a range of severities (UCMD, intermediate-COL6-RM and BM). We found a distinctive pattern of regional adipose tissue accumulation which was more evident in children at the most severe end of the spectrum. In particular, the accumulation of fat in the android region was a distinguishing feature of UCMD patients. In parallel, there was a decrease in lean mass compatible with a state of sarcopenia, particularly in ambulant children with an intermediate phenotype. All children and adult patients that were sarcopenic were also obese. These changes were significantly more pronounced in children with collagen VI deficiency than in children with Duchenne Muscular Dystrophy of the same ambulatory status. High molecular weight adiponectin and leptin were significantly increased in sera from children in the intermediate and BM group. Correlation analysis showed that the parameters of fat mass were negatively associated with motor function according to several validated outcome measures. In contrast, lean mass parameters correlated positively with physical performance and quality of life. Leptin and adiponectin circulating levels correlated positively with fat mass parameters and negatively with lean mass and thus may be relevant to the disease pathogenesis and as circulating markers. Taken together our results indicate that COL6-RM are characterized by specific changes in total fat mass and distribution which associate with disease severity, motor function and quality of life and which are clinically meaningful and thus should be taken into consideration in the management of these patients.